The Vaccinia Virus A36R Protein Is a Type Ib Membrane Protein Present on Intracellular but Not Extracellular Enveloped Virus Particles - Van Eijl, H; Hollinshead, M; Smith, G (Elsevier, 2000)
Vaccinia virus gene A36R encodes a 45-kDa protein that is conserved in orthopoxviruses. A virus lacking the A36R protein formed a small plaque, was unable to induce the polymerization of actin tails, and was avirulent in vivo. Here we present a further characterization of the A36R protein by in vitro transcription and translation and analysis of infected cells by confocal microscopy and immunoelectron microscopy of cryosections using a monoclonal antibody raised against the C-terminal domain of the A36R protein. Translation of the A36R mRNA in vitro produced a protein of the same size whether or not the translation reaction was performed in the presence of canine pancreatic microsomes. However, the polypeptide synthesized in the presence of microsomes was associated integrally with the membrane and was sensitive to digestion by exogenous protease without permeabilization of the membrane with detergent, indicating that the majority of the protein is exposed on the outside of the vesicle. Consistent with this, immunofluorescent analysis of virus-infected cells demonstrated that the C-terminal domain of A36R was not exposed on the cell surface but was detected once the cell membrane was permeabilized. Immunoelectron microscopy of cryosections of infected cells showed that the protein was absent from IMV particles but present on intracellular enveloped virus (IEV) particles, predominantly on the cytosolic face of the IEV outer membrane. Where cell-associated enveloped virus (CEV) particles were attached to the cell surface, the A36R protein was detected only on the cytosolic surface of the plasma membrane where the virus particle remained attached to the cell and not elsewhere on the plasma membrane or on the CEV particle. A36R and actin copurified with EEV particles due to the association of fragments of cellular membranes with the EEV particles. Therefore, A36R represents the first example of a virus-encoded protein that is present on IEV but not CEV particles.